Development and validation of the multiple sclerosis questionnaire for the evaluation of job difficulties (MSQ‐Job). (18th February 2015) - Raggi, A.; Giovannetti, A. M.; Schiavolin, S.; Confalonieri, P.; Brambilla, L.; Brenna, G.; Cortese, F.; Covelli, V.; Frangiamore, R.; Moscatelli, M.; Ponzio, M.; Torri Clerici, V.; et al.
<x xml:space="preserve">Abstract</x> Objective Multiple sclerosis (MS) affects young adults of working age. Difficulties in work‐related activities are usually ascribed to MS symptoms, while the impact of workplace features is underestimated. This article presents the Multiple Sclerosis Questionnaire for Job Difficulties (MSQ‐Job), designed to assess working difficulties due to MS symptoms and workplace features. Methods A sample of employed MS patients completed the MSQ‐Job, the WHO‐Disability Assessment Schedule (WHODAS 2.0) and the 54‐items MS Quality of Life Questionnaires (MSQOL‐54); the expanded disability status scale (EDSS) was used to define MS severity. Factor structure was evaluated using principal component extraction and Oblimin rotation; internal consistency was assessed with Cronbach's alpha; construct and discriminant validity using t‐test (EDSS 0‐2 vs >2; patients self‐reporting need for support vs patients reporting no needs; full‐time vs part‐time employees); and Pearson's correlation with WHODAS 2.0 and MSQOL‐54. Results The MSQ‐Job is a 42‐item questionnaire with six scales and an overall factor. Scores range on a 0–100 scale (higher scores indicate more and more severe difficulties); patients with EDSS>2 and self‐reporting support needs had worse scores than those with EDSS 0‐2 and without needs. Correlations with WHODAS 2.0 and MSQOL‐54 were generally significant (P < 0.0007) and below 0.70. Conclusions The MSQ‐Job jointly measures the impact of respondents' symptoms and workplace features on work activities and enables to assess the effects of clinical and occupational interventions and better describe the impact of MS indirect costs.